DEVELOPMENT OF SKILLS OF SELF-CONTROL OF LEARNING ACTIVITY IN UNIVERSITY STUDENTS - Azizbek Botirov (European Journal of Interdisciplinary Research and Development, 2023)
This scientific article examines the importance and need for specialists who are able not only to generate ideas and develop projects, but also to organize cost-effective production and release of competitive products. In a market economy with fierce competition, highly qualified personnel are required who are capable of creative work and the search for effective forms of organizing activities. The article focuses on the importance of self-control in the educational activities of students, as the basis for the formation of skills for checking and correcting their work. Various approaches to defining the essence of self-control consider it as a property of a person, an act of mental activity, a component of educational activity and a method of selfregulation of behaviour. The authors of the study consider self-control of students of a technical university in the context of the development of self-control skills and the formation of personality traits. The study shows that first-year students have a level of formation of selfcontrol skills that meets the requirements of high school.